Planting Saved Roundup Ready 1 Soybean Seed Implications on Yield and Profit. (1st March 2017) - Mason, Stephen C.; Walters, Cory G.; Galusha, Tomie D.; Wilson, Roger K.; Kmail, Zaher
Abstract : Core Ideas: RR1 Soybean seed produces similar yield to RR2Y seed. Saving RR1 soybean affords large economic advantages with lower risk. Saved RR1 soybean seed had similar yield, bulk densities, and percent lodging as commercial RR2Y seed. A 3‐yr study was conducted to address agronomic considerations and economic feasibility for the legal right for Nebraska farmers to plant saved seed of Roundup Ready (RR1) (Monsanto Company, St. Louis, MO) soybean [ Glycine max (L). Merr.] varieties rather than purchasing commercial Genuity (Monsanto Company, St. Louis, MO) Round Ready 2 Yield (to be referred to as RR2Y throughout the rest of the manuscript) seed. We hypothesized that net income from producing saved RR1 seed would be greater than for RR2Y seed when yield and cost differentials related to seed source, storing and cleaning seed were considered. Commercial RR1 and RR2Y seed in 2012, and saved RR1 and commercial RR2Y soybean seed in 2013 and 2014 produced no differences in average yields, bulk densities, and percent lodging. Plant population differences at harvest were present across years, but saved RR1 and commercial RR2Y seed plant populations were similar, and did not influence soybean yield. Saved RR1 seed had similar purity, germination, and vigor compared to seed tag information for commercial RR2Y seed. Gross returns to saving seed efforts were estimated to be between US66.15 and 85.27 ha −1 over commercial RR2Y seed. If producers can obtain approval for use of competitively yielding public or private RR1 soybean variety seed and put in the extra effort required to produce, handle, clean, and save seed, a substantial increase in net income is possible by planting saved RR1 seed rather than purchasing commercial RR2Y seed. Producers will need to learn about the relative costs and benefits of saved RR1 and commercial RRY2 seed to make an informed decision.